Examining the Change in Foreign Policy Paradigm and the Impact of Political Parties in the United States: A Case Study of the Brittney Griner and Viktor Bout Prisoner Exchange - Ofel Abiwada Abimanyu; Jatmika, Muhammad Indrawan (Talenta Publisher, 2024)
The decision by the United States to exchange Viktor Bout, a notorious arms smuggler and former international fugitive, for Brittney Griner, a prominent female basketball player, has generated considerable controversy and debate. A key point of contention centers on the stark divergence of this policy from the transactional approach adopted during the previous Donald Trump administration. Concurrently, some factions contend that the exchange of Brittney Griner for Viktor Bout reflects a political agenda championed by the Democratic Party, thereby fostering the perception that liberal interests receive preferential treatment within the Joe Biden administration's cabinet. This research aims to examine the change in foreign policy paradigm in the United States and the impact of political parties in the context of the prisoner exchange between Brittney Griner and Viktor Bout. The exchange has garnered public attention as it raises questions about the shift in the United States' foreign policy approach and the influence of political parties in the decision-making process. This study adopts a qualitative approach by analyzing relevant sources such as academic literature, news reports, and official government statements. The findings reveal a paradigm shift in the United States' foreign policy during the Joe Biden administration. The transactional approach adopted by former President Donald Trump has been replaced by a values-based orientation and the nation's obligation to protect its citizens wherever they may be. The prisoner exchange between Griner, an American athlete, and Bout, a Russian detainee, serves as evidence of this change.